Construction and demolition waste as partial cement replacement. Issue 9 (8th June 2018) - Rocha, Sabina; Sousa-Coutinho, Joana
Abstract : In recent years several studies have been carried out using waste from various industries to partially replace cement in concrete. In addition to improving concrete durability, the use of these waste materials also contributes to reducing emissions, mainly carbon dioxide, and to saving resources. In this study, the applicability of finely ground construction and demolition waste (CDWg ) in concrete as a partial substitute for Portland cement was evaluated and the effects on durability were assessed. Mortars and pastes with cement replacements of 0%, 5% (CDWg 5) and 10% (CDWg 10) were produced. The different mortar types were tested to ascertain their 7, 28 and 90 d strengths and durability-related properties, including capillary absorption, chloride diffusion, accelerated carbonation, resistance to alkali–silica reaction (ASR) and sulfate attack. Mortar containing CDWg performed better than the control only with regard to expansion due to ASR. In the other tests, mortar containing CDWg did not attain the performance of the control specimens. However, for the CDWg 5 mortar, performance losses were not significant, indicating that this particular waste at this dosage may be used to partially replace Portland cement. A replacement of 10% could be considered in concretes with lower levels of performance requirements.